1979
DOI: 10.1128/jcm.10.1.111-113.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymes on rotavirus infectivity

Abstract: The infectivity of a bovine rotavirus was enhanced 140-, 8-, and 3-fold, respectively, by trypsin, protease, and lactase. Ficin, carboxypeptidases A and B, lysozyme, and ,B-galactosidase had little effect on the infectivity. Chymotrypsin caused a threefold decrease in the infectivity. Trypsin acts directly on the rotavirus and not on the host cell. Previous enzyme studies (9, 13-15) with reoviruses have shown the following: (i) the infectivity of reoviruses can be enhanced by at least eight different proteolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Rotaviruses are, in general, difficult to isolate and to grow in cell cultures using conventional techniques. However, certain strains may be serially propagated in cell cultures if the virus inuculum is treated with proteolytic enzymes or if proteolytic enzymes are incorporated into the medium after infection (1,2,3,6,16,40,41,44,45,49,56). ENGI, A~D and POSTON (9) reported that rotavirus observed in feces by E?¢[ from a diarrheal dog grew in cell cultures with the aid of trypsin, but did not grow in cell cultures without trypsin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rotaviruses are, in general, difficult to isolate and to grow in cell cultures using conventional techniques. However, certain strains may be serially propagated in cell cultures if the virus inuculum is treated with proteolytic enzymes or if proteolytic enzymes are incorporated into the medium after infection (1,2,3,6,16,40,41,44,45,49,56). ENGI, A~D and POSTON (9) reported that rotavirus observed in feces by E?¢[ from a diarrheal dog grew in cell cultures with the aid of trypsin, but did not grow in cell cultures without trypsin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors and antibody were present overnight. Positive controls for the effect of weak bases on intravesicular pH were provided by infection of treated MA104 cell monolayers with reovirus types 1 and 3 (MOI, 5). After 24 h the reovirus-infected monolayers were freezethawed three times, and viral titers were determined by plaque assay.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of trypsin on viral infectivity is mediated by alteration of the virion rather than the cell surface (5,19). The outer shell of the rotavirus capsid is formed by two proteins, viral proteins 3 and 7 (VP3 and VP7, respectively), which are the products of genes 4 and 9, respectively (35).…”
mentioning
confidence: 99%
“…In vitro, this is simulated by controlled incubation with trypsin. Trypsin activation is necessary for rapid internalization and infection (6,18); uncleaved rotavirus is internalized slowly and is not infectious (17,25). Trypsin cleaves the VP4 spike protein at two highly conserved sites (Arg-241 and Arg-247) to yield two peptides, VP8* (28 kDa) and VP5* (65 kDa), which remain attached to the outer capsid (16,29).…”
mentioning
confidence: 99%